Behavioural effects of APH199, a selective dopamine D4 receptor agonist, in animal models - Chestnykh, Daria; Graßl, Fabian; Pfeifer, Conrad; Dülk, Jonas; Ebner, Chiara; Walters, Mona; von Hörsten, Stephan; Kornhuber, Johannes; Kalinichenko, Liubov; Heinrich, Markus; Müller, Christian P. (Psychopharmacology, 2023)
Rationale: The dopamine D4 receptors (DRD4) play a key role in numerous brain functions and are involved in the pathogenesis of various psychiatric disorders. DRD4 ligands have been shown to moderate anxiety, reward and depression-like behaviours, and cognitive impairments. Despite a series of promising but ambiguous findings, the therapeutic advantages of DRD4 stimulation remain elusive. Objectives: The investigation focused on the behavioural effects of the recently developed DRD4 agonist, APH199, to evaluate its impact on anxiety, anhedonia, behavioural despair, establishment and retrieval of alcohol reinforcement, and amphetamine (AMPH)-induced symptoms. Methods: Male C57BL/6 J mice and Sprague–Dawley rats were examined in five independent experiments. We assessed APH199 (0.1–5 mg/kg, i.p.) effects on a broad range of behavioural parameters in the open field (OF) test, conditioned place preference test (CPP), elevated plus maze (EPM), light–dark box (LDB), novelty suppressed feeding (NSF), forced swim test (FST), sucrose preference test (SPT), AMPH-induced hyperlocomotion test (AIH), and prepulse inhibition (PPI) of the acoustic startle response in AMPH-sensitized rats. Results: APH199 caused mild and sporadic anxiolytic and antidepressant effects in EPM and FST, but no remarkable impact on behaviour in other tests in mice. However, we found a significant increase in AMPH-induced hyperactivity, suggesting an exaggeration of the psychotic-like responses in the AMPH-sensitized rats. Conclusions: Our data challenged the hypothesis of the therapeutic benefits of DRD4 agonists, pointing out a possible aggravation of psychosis. We suggest a need for further preclinical studies to ensure the safety of antipsychotics with DRD4 stimulating properties.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Alcohol; Anxiety; APH199; Depression; DRD4 agonist; Psychosis; Schizophrenia

Electrophotographic 3D printing of pharmaceutical films - Kopp, Sebastian-Paul; Medvedev, Vadim; Tangermann-Gerk, Katja; Wöltinger, Natalie; Rothfelder, Richard; Graßl, Fabian; Heinrich, Markus; Januskaite, Patricija; Goyanes, Alvaro; Basit, Abdul W.; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
The usage of three-dimensional (3D) printing in pharmaceutical applications offers significant advantages compared to conventional manufacturing approaches such as tableting or encapsulation. Laser sintering (LS), also referred to as powder bed fusion – laser beam (PBF-LB), formerly also known as selective laser sintering (SLS), offers the production of pharmaceuticals directly from a powder mixture with high geometrical flexibility and adjustable release profiles. However, due to limitations of conventional powder application methods for PBF-LB, neither the material composition nor the material distribution can be tailored within a printed layer. To overcome these restrictions, electrophotographic powder application (EPA), a novel method for selective powder application, was utilized in this study. EPA allows the deposited layer thickness to be reduced to values between 12 and 76 µm, depending on the used pharmaceutical powder blend. Thus, the laser energy input required for interlayer connection can be reduced, enabling the use of a CO2 laser. In this study, for the first time, EPA in combination with powder bed fusion – laser beam of polymers (EPA-PBF-LB/P) was utilized to successfully deposit and print three different model drugs: paracetamol, nicotinamide, and caffeine, mixed with Eudragit L 100–55, a pharmaceutical grade polymer. Through the use of EPA, thin layers of powder blends were successfully deposited in the build chamber, leading to no thermal degradation of the polymer or drugs from the use of a CO2 laser. Single- and multi-material pharmaceutical films were successfully printed via EPA-PBF-LB, utilizing EPA to selectively as well as precisely apply different powders within a single layer into the build chamber. This introduces a novel method of printing pharmaceuticals using SLS with a CO2 laser and without the use of additional colorants.<br
Keywords: Additive manufacturing; Electrophotography; Printed pharmaceuticals; Laser powder bed fusion; Laser sintering; Multi-material printing

Exploring Structural Determinants of Bias among D4 Subtype-Selective Dopamine Receptor Agonists - Graßl, Fabian; Bock, Leonard; Huete-Huerta González, Álvaro; Schiller, Martin; Gmeiner, Peter; König, Jörg; Fromm, Martin; Hübner, Harald; Heinrich, Markus (Journal of Medicinal Chemistry, 2023)
The high affinity dopamine D4 receptor ligand APH199 and derivatives thereof exhibit bias toward the Gi signaling pathway over β-arrestin recruitment compared to quinpirole. Based on APH199, two novel groups of D4 subtype selective ligands were designed and evaluated, in which the original benzyl phenylsemicarbazide substructure was replaced by either a biphenylmethyl urea or a biphenyl urea moiety. Functional assays revealed a range of different bias profiles among the newly synthesized compounds, namely, with regard to efficacy, potency, and GRK2 dependency, in which bias factors range from 1 to over 300 and activation from 15% to over 98% compared to quinpirole. These observations demonstrate that within bias, an even more precise tuning toward a particular profile is possible, which─in a general sense─could become an important aspect in future drug development. Docking studies enabled further insight into the role of the ECL2 and the EPB in the emergence of bias, thereby taking advantage of the diversity of functionally selective D4 agonists now available.
CRIS-Team Scopus Importer:2023-08-11

Identification and Quantification of Resveratrol and Its Derivatives in Franconian Wines by Comprehensive Liquid Chromatography-Tandem Mass Spectrometry - Hoferer, Laura; Rodrigues Guimarães Abreu, Vera Lúcia; Graßl, Fabian; Fischer, Oliver; Heinrich, Markus; Gensberger-Reigl, Sabrina (ACS Food Science & Technology, 2023)
Resveratrol and its derivatives are valued compounds in foods such as wine. To date, their occurrence and concentrations in Franconian wines are not known. Thus, the present study investigated resveratrol and its derivatives in Franconian wines. First, comprehensive ultrahigh-performance liquid chromatography (UHPLC)-tandem mass spectrometry methods were applied to identify cis-/trans-resveratrol, cis-/trans-piceid, deoxyrhapontigenin, trans-piceatannol, and cis-/trans-astringin. Second, a sensitive UHPLC-scheduled multiple reaction monitoring method for absolute quantification of the major resveratrol derivatives was developed, validated, and applied to 19 Franconian wine samples. Recovery rates ranged between 95.0 and 109.3% and reproducibility between 2.6 and 10.3%. The limits of detection/quantification were between 0.01 and 0.08 μg/mL. The samples contained 0.07-2.61 μg/mL cis-resveratrol, 0.05-3.82 μg/mL trans-resveratrol, 0.24-9.01 μg/mL cis-piceid, and 0.25-8.30 μg/mL trans-piceid. Additionally, the concentrations of deoxyrhapontigenin (0.02-0.53 μg/mL), trans-piceatannol (0.05-1.35 μg/mL), and trans-astringin (0.04-0.67 μg/mL) were quantified.
CRIS-Team Scopus Importer:2023-07-07
Keywords: piceid; precursor ion scan; resveratrol; scheduled multiple reaction monitoring; stilbene derivatives; UHPLC−MS/MS; wine

Tuning the Polarity of Antibiotic-Cy5 Conjugates Enables Highly Selective Labeling of Binding Sites - Graßl, Fabian; Konrad, Maike; Krüll, Jasmin; Pezerovic, Azra; Zähnle, Leon; Burkovski, Andreas; Heinrich, Markus (Chemistry - A European Journal, 2023)
Multidrug-resistant bacteria pose a major threat to global health, even as newly introduced antibiotics continue to lose their therapeutic value. Against this background, deeper insights into bacterial interaction with antibiotic drugs are urgently required, whereas fluorescently labeled drug conjugates can serve as highly valuable tools. Herein, the preparation and biological evaluation of 13 new fluorescent antibiotic-Cy5 dye conjugates is described, in which the tuning of the polarity of the Cy5 dye proved to be a key element to achieve highly favorable properties for various fields of application.
CRIS-Team Scopus Importer:2023-07-28
Keywords: antibiotics; cyanines; dye conjugates; fluorescence; microscopy